Understanding veterinary drug shop workers' knowledge and practices to identify drivers of antibiotic use in Vietnamese livestock farms - Nohrborg, S.; Thinh Nguyen-Thi; Huyen Nguyen Xuan; Yen Luu Thi Hai; Lindahl, Johanna F.; Boqvist, S.; Järhult, J.D.; Magnusson, Ulf (Wiley, 2024)
Background: Antimicrobial resistance (AMR) is a One Health issue and a major threat to animal and human health. Antibiotic use (ABU) drives AMR development, and several hotspots for ABU, and AMR, in livestock have been identified in Southeast Asia, including Vietnam. There are often multiple drivers of ABU at farms, and to identify all of them there is a need to look beyond farm level.